Biological Significance of GPCR Heteromerization in the Neuro-Endocrine System - Jockers, Ralf; Kamal, Maud (Frontiers in Endocrinology, 2011)
Clustering of proteins in higher order complexes is a common theme in biology and profoundly influences protein function. The idea that seven-transmembrane spanning G protein-coupled receptors (GPCRs) might form dimers or higher order oligomeric complexes has been formulated more than 20 years ago. Since then, this phenomenon has been investigated with many different biochemical and biophysical techniques. The more recent notion of GPCR heteromerization describes the specific association of two different GPCRs. GPCR heteromerization may be of primary importance in neuroendocrinology, as this may explain at least some of the functional crosstalks described between different hormonal systems. Importantly, many GPCR heteromers have distinct functional properties compared to their corresponding homomers. Heteromer-specific pharmacological profiles might be exploited for drug design and open new therapeutic options. GPCR heteromerization has been first studied in heterologous expression systems. Today, increasing evidence for the existence of GPCR heteromers in endogenous systems is emerging providing crucial evidence for the physiological function of GPCR heteromerization.